Electrospinning of alcell lignin for the preparation of ORR electrocatalysts - Ruiz-Rosas, Ramiro Rafael; Cordero-Alcántara, Tomás; Rodríguez-Mirasol, José; Rosas-Martínez, Juana María; García-Mateos, Francisco José (My University, 2019)
Carbon fibers are one of the components of the electrode assemblies used in fuel cells. They are usually prepared from polyacrylonitrile, a non-renewable synthetic polymer. Lignin is a highly abundant biopolymer that is obtained in large amounts as a byproduct in the papermaking and biofuel industries. It can be used as renewable precursor in the production of carbon fibers. In this sense, we have reported the production of carbon microfibers by coaxial electrospinning of Alcell lignin [1]. It is also possible to load platinum on these fibers, obtaining excellent catalysts for methanol oxidation [2]. In this work we report the production of electrocatalysts for the oxygen reduction reaction (ORR) via electrospinning of Alcell lignin/metallic salt solutions, enabling the replacement of synthetic polymers as raw material. [1] R. Ruiz-Rosas, J. Bedia, M. Lallave, I.G. Loscertales, A. Barrero, J. Rodríguez-Mirasol, T. Cordero, The production of submicron diameter carbon fibers by the electrospinning of lignin, Carbon. 48 (2010) 696–705. [2] F.J. García-Mateos, T. Cordero-Lanzac, R. Berenguer, E. Morallón, D. Cazorla-Amorós, J. Rodríguez-Mirasol, T. Cordero, Lignin-derived Pt supported carbon (submicron)fiber electrocatalysts for alcohol electro-oxidation, Applied Catalysis B: Environmental. 211 (2017) 18–30.
Keywords: Fibras de carbono; Catalizadores; Electrospinning; Lignin; QRR; Fuel cell; Electrocatalyst